USING ANTONYMS PAIR IN PROVERBS AND SAYINGS - Shoimov, Shavkat (Журнал иностранных языков и лингвистики, 2021)
The article dedicated to the use antonyms in English proverbs and sayings. Stylistic and grammatical features of words also analyzed and compared.